Serangga yang berasosiasi dengan puru daun eukaliptus di Sumatra Utara - Syawaluddin Syawaluddin; Purnama Hidayat; Nina Maryana (Perhimpunan Entomologi Indonesia, 2019)
Eucalyptus spp. are commonly cultivated in the forest industry sector as the raw material for the pulp and paper industry. One of the problems in Eucalyptus plantations is leaf galls caused by insects. Leaf galls can cause leaf damage and inhibit plant growth. The objective of this study was to identify insects associated with leaf galls on eucalyptus plants. Leaves with gall symptoms were collected in the Tele sector located between Humbang Hasundutan and Samosir Regencies, North Sumatra Province. Identification was based on morphological characters of the antenna, dorsal mesosoma, fore wings, and hind legs. Results showed that there were seven insect species associated with leaf galls on Eucalyptus, i.e. Ophelimus eucalypti (Gahan) (Eulophidae) pest gall on eucalyptus leaf, Eurytoma sp. Illiger (Eurytomidae), Aprostocetus sp. Westwood, Quadrastichus mendeli Kim & La Salle, Chrysonotomyia germanica (Erdös), and Closterocerus chamaeleon (Girault) (Eulophidae) acts as a parasitoid and Diplesiostigma bisetosum Boucek (Tetracampidae).